Electrochromic response of pulsed laser deposited oxygen deficient monoclinic β-MoO3 thin films. (10th September 2020) - Santhosh, S.; Nanda Kumar, A.K.; Kennedy, J.; Subramanian, B.
Abstract: β-molybdenum trioxide (β-MoO3 ) films that crystallize in the monoclinic structure were successfully fabricated using pulsed laser deposition (PLD) technique by varying the partial pressure of reactive oxygen P(O2 ) gas ranges form 10 −1 mbar to 10 −6 mbar. The electrochromic (EC) properties of these films were presented in this report as a function of P(O2 ). The composition of the films was calculated from X-ray photoelectron Spectroscopy (XPS) and Electron energy dispersive spectroscopy (EDS) analysis. After Li + intercalation, the films prepared at lower P(O2 ) (viz 10 −4 mbar, 10 −5 mbar and 10 −6 mbar) formed new stable phase of Li2 MoO4 whereas no stable phase formation was observed in the films coated at higher P(O2 ) after Li + intercalation. The EC studies revealed that the films coated at 10 −2 mbar P(O2 ) had good coloration efficiency (η) of about 66 × 10 −4 m 2 /C and 83% reversibility whereas the films coated with 10 −6 mbar P(O2 ) showed lower coloration efficiency of 11 × 10 −4 m 2 /C and 13% reversibility. But interestingly, the lower oxygen deficient film prepared at 10 −1 mbar had lower EC response compared to higher oxygen deficient film 10 −2 mbar. So, it is of interest to study comparatively the material properties of Li + intercalated and de-intercalated 10 −2 mbar and 10 −6 mbar films (extreme values of EC properties). Analysis of these films suggested that the 10–20 wt% oxygen deficiency forms vacancies in the lattice which gave way to intercalate/deintercalate Li + freely in to it. The EC performance of stoichiometric and more deficient MO films were found to be poor whereas few (10–20%) oxygen deficient MO films showed better EC performance.